Using Archives to Analyze Online Curricular Structures at a Community College - Hai-Jew, Shalin (My University, 2010)
Using qualitative inductive analytical approaches, this paper examined the curricular structures of twenty-two (22) online courses (both fully online and hybrid) randomly chosen from Shoreline Community College’s (SCC) course archives to explore how structural elements enhance online learner interactivity and experiences.
Keywords: Online courses; Curriculum